Andrew Whitley: Bread Matters: The state of modern bread - MacGuire, James (Petits Propos Culinaires, 2007)
Andrew Whitley: Bread Matters: The state of modern bread: Fourth Estate, 2006: ISBN 0007203748: 371 pp., £20.